ANSWER
x = 2, y = -0.5
Step-by-step explanation
We have two equations in the system of equations:
3x - 2y = 7
9x + 4y = 16
To use the addition method, we have to make the coefficients of one variable in one equation, the same as in the second equation.
Let us make the coefficient of y the same in the two equations.
We do that by multiplying the first equation by 2:
2(3y - 2y) = 2(7)
=> 6y - 4y = 14
Now we have:
6y - 4y = 14
9x + 4y = 16
Add them together:
6x - 4y = 14
+ (9x + 4y = 16)
=> 15x + 0 = 30
=> 15x = 30
x = 30 / 15
x = 2
Put that in the first equation:
3x - 2y = 7
3(2) - 2y = 7
6 - 2y = 7
=> 2y = 6 - 7
2y = -1
=> y = -1/2
y = -0.5
Therefore, x = 2, y = -0.5